Composition measurements of the 1989 Arctic winter stratosphere by airborne infrared solar absorption spectroscopy - Toon, G. C.; Farmer, C. B.; Schaper, P. W.; Lowes, L. L.; Norton, R. H. (1992)
The paper reports simultaneous measurements of the stratospheric burdens of H2O, HDO, OCS, CO2, O3, N2O, CO, CH4, CF2Cl2, CFCl3, CHF2Cl, C2H6, HCN, NO, NO2, HNO3, ClNO3, HOCl, HCl, and HF made by the JPL MkIV interferometer on board the NASA DC-8 aircraft during January and early February 1989 as part of the Airborne Arctic Stratosphere Experiment. Data were obtained on 11 flights at altitudes of up to 12 km over a geographic region covering the NE Atlantic Ocean, Iceland, and Greenland. Analyses of the chemically active gases reveal highly perturbed conditions within the vortex. The ClNO3 abundance was chemically enhanced near the edge of the vortex but was then depleted inside. NO2 was severely depleted inside the vortex. In contrast to Antarctica, H2O and HNO3 were both more abundant inside the vortex than outside. It is suggested that although the Arctic vortex did not get cold enough to produce any dehydration, or as vertically extensive denitrification as occurred in Antarctica, nevertheless, enough heterogeneous chemistry occurred to convert over 90 percent of the inorganic chlorine to active forms in the 14- to 27-km altitude range by early February 1989.